The Health Education Concerning the Influence Of Knowledge And Attitudes On The “Concise, Neat, Clean, Careful, Diligent” Work Culture Behavior Of Employees - Rachmawaty, Ikke Winar; Wardani, Ratna (Chakra Brahmanda Lentera Institute, 2023)
Background: Training and socialization on Occupational Health and Safety (OHS) throughout 2022 have been carried out to achieve ISO. From the audit results in 2023, it has been found, among others, that the application of “Concise, neat, clean, careful, and diligent” needs to be developed further. The purpose of this activity is to provide Dinas Kesehatan Kabupaten Kediri Kediri employees with knowledge about “Concise, Neat, Clean, Careful, Diligent”. Methods: Participants in this activity were Dinas Kesehatan Kabupaten Kediri employees, and the methods used were lectures, discussions, and questions and answers. The data collection technique used was a questionnaire. Results: The results of the pre-test and post-test showed that only a small proportion had good knowledge (37%), positive attitudes towards the “Concise, Neat, Clean, Careful, Diligent” (30%), and good “Concise, Neat, Clean, Careful, Diligent” behaviour (33%). It was found that a p-value of 0.001 <0.05 indicated that there was a significant influence between “Concise, Neat, Clean, Careful, Diligent” knowledge and “Concise, Neat, Clean, Careful, Diligent” behaviour and a p-value of 0.010 <0.05 indicated that there was a significant influence between the “Concise, Neat, Clean, Careful, Diligent” attitudes and “Concise, Neat, Clean, Careful, Diligent” behavior of Dinas Kesehatan Kabupaten Kediri employees. Conclusion: This community service activity went smoothly, thanks to the extraordinary enthusiasm of the employees in following all the planned activities. This activity positively impacted and refreshed information about the “Concise, Neat, Clean, Careful, Diligent” Work Culture, contributing to increased knowledge, especially for employees. In addition, this service effort also received support and appreciation from the Dinas Kesehatan Kabupaten Kediri office